Japanese guidelines for the management of pemphigus. Issue 6 (June 2014) - Committee for Guidelines for the Management of Pemphigus Disease; Amagai, Masayuki; Tanikawa, Akiko; Shimizu, Tomoko; Hashimoto, Takashi; Ikeda, Shigaku; Kurosawa, Michiko; Niizeki, Hironori; Aoyama, Yumi; Iwatsuki, Keiji; Kitajima, Yasuo
Abstract The Committee for Guidelines for the Management of Pemphigus was organized as one element of the Japanese Dermatological Association (JDA) and the Ministry of Health, Labour, and Welfare (MHLW) Research Project on Measures for Research Committee for Intractable Skin Disease. Pemphigus has been defined as a group of intractable autoimmune blistering diseases caused by anti‐desmoglein 1 and/or anti‐desmoglein 3 IgG autoantibodies by the MHLW. The diagnosis of this condition and the criteria for assessing its severity are based on suggestions from the MHLW Research Group. The clinical practice guidelines presented here are those that are currently recommended in Japan. However, symptoms and complications can vary widely among individual pemphigus patients, so not all therapies will be required to be in complete agreement with these guidelines.